Negotiation of Javanese culture in the tradition of respecting guests in Serat Jatiswara - Pipit Mugi Handayani; Priscila Fitriasih Limbong; Turita Indah Setyani (Diksi, 2026)
This study examines the process of negotiation of Javanese culture in receiving guests based on dynamics of relationship between Javanese figures and non-Javanese figures (Campa) in Serat Jatiswara. Serat Jatiswara is an eighteenth-century suluk work that explores Islamic teachings in the form of a Macapat song. This manuscript represents the life of the Javanese rural people and their traditional mindset. Javanese characters in the text exhibit a responsive and adaptive attitude towards the presence of Jatiswara, who is treated as a great guest. This study focused on ideological negotiations through the pattern of relationship between Jatiswara and Javanese figures. This is text analysis research by using Gramsci negotiation theory to elaborate dynamics of relationship between Javanese figures and non-Javanese figures. The results showed that Jatiswara, a traveler from Campa who sought out his younger brother and spread Islam, was positioned superior to the Javanese figures he visited. The main findings include: (1) the representation of respect for guests, (2) the domination-subordination relationship through the glorification of Jatiswara, and (3) the accommodating attitude of the Javanese people. These findings confirm that Serat Jatiswara reflects the Javanese cultural ideology, namely harmonization, through the strategy of character representation and social relations as a negotiation of Javanese identity.